2016
DOI: 10.21037/atm.2016.08.65
|View full text |Cite
|
Sign up to set email alerts
|

New role of biomarkers: mid-regional pro-adrenomedullin, the biomarker of organ failure

Abstract: Mid-regional pro-adrenomedullin (MR-proADM) has a good biomarker profile: its half-life is several hours, and its plasma concentrations can be determined in clinical practice, it is essentially irrelevant, but proportionally represents the levels and activity of adrenomedullin (ADM). ADM synthesis is widely distributed in tissues, including bone, adrenal cortex, kidney, lung, blood vessels and heart. Its fundamental biological effects include vasodilator, positive inotropic, diuretic, natriuretic and bronchodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 65 publications
4
71
0
1
Order By: Relevance
“…11 To overcome this hurdle, we measured levels of pro-ADM, a biologically inactive yet chemically stable mid-region precursor of ADM that is released together with ADM at a 1:1 ratio; has a half-life of several hours; and has been used as a surrogate for ADM in other diseases. 12,13 Serum pro-ADM levels were significantly elevated in acute SCLS sera compared to either convalescent SCLS sera or sera from healthy controls (Figure 3A). There appeared to be two distinct groups: one with relatively high pro-ADM levels during the acute phase, and another with significantly lower values ( p <0.0001, Mann-Whitney).…”
Section: Resultsmentioning
confidence: 96%
“…11 To overcome this hurdle, we measured levels of pro-ADM, a biologically inactive yet chemically stable mid-region precursor of ADM that is released together with ADM at a 1:1 ratio; has a half-life of several hours; and has been used as a surrogate for ADM in other diseases. 12,13 Serum pro-ADM levels were significantly elevated in acute SCLS sera compared to either convalescent SCLS sera or sera from healthy controls (Figure 3A). There appeared to be two distinct groups: one with relatively high pro-ADM levels during the acute phase, and another with significantly lower values ( p <0.0001, Mann-Whitney).…”
Section: Resultsmentioning
confidence: 96%
“…ADM is produced as a precursor protein called preproadrenomedullin in numerous tissues including adrenal glands, endothelium, vascular smooth muscles, renal parenchyma, and cardiomyocytes. This protein undergoes complex processing, first generating pro-ADM, which subsequently is cleaved into multiple peptides including mid-regional proADM (MR-proADM) and ADM; the latter can exist in both a bioactive amidated form (bio-ADM) and a glycated inactive form [140]. Whether MR-proADM has biological activity is unclear, but because it is more stable than ADM, it is the preferred biomarker.…”
Section: Inflammation Marker Admmentioning
confidence: 99%
“…Whether MR-proADM has biological activity is unclear, but because it is more stable than ADM, it is the preferred biomarker. Like PCT, MRproADM is strongly elevated in sepsis and could be used as a prognostic marker and to guide the diagnosis and treatment of sepsis [140]. MR-proADM lacks specificity for the diagnosis of HF, but the BACH study demonstrated that MR-proADM had superior accuracy for predicting 90-day mortality compared with BNP in acute HF [141].…”
Section: Inflammation Marker Admmentioning
confidence: 99%
“…Pro-ADM, with a half-life of a few hours, peaks between 24 to 48 hours after onset of symptoms of myocardial infarction. [60][61][62] While it has not been shown to have utility in the early diagnosis of myocardial infarction, it may be prognostic of adverse outcomes and all-cause mortality among patients presenting with acute chest pain. 31,63 Elevated levels are seen in other cardiovascular conditions, including congestive heart failure 64,65 and hypertension, 66 as well as noncardiovascular conditions such as systemic inflammatory states 67 and type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%